Phase Engineering and Alkali Cation Stabilization for 1T Molybdenum Dichalcogenides Monolayers. (28th June 2022) - Liu, Fu; Zou, Yiming; Tang, Xiaoyu; Mao, Lei; Du, Dou; Wang, Helin; Zhang, Min; Wang, Zhiqiao; Yao, Ning; Zhao, Wenyu; Bai, Miao; Zhao, Ting; et al.
Abstract: The technological barriers of the dimensional engineering and interfacial instability seriously hinder the scalable production of metallic (1T) transition metal dichalcogenides (TMD) monolayers. In this article, a facile and fast electron injection strategy is developed to modulate the d orbits of Mo center in trigonal prismatic 2H phases (MoS2 and MoSe2 ); meanwhile various cations (Li +, Na +, and K + ) reinforce the in‐plane 1T‐atomic arrangement and expand the out‐of‐plane spacing for easy exfoliation. Theoretical and experimental evaluations further elucidate the decisive electron‐donating capability and suitable ionic radius in stabilizing 1T coordination. The as‐tailored 1T‐MoS2 /MoSe2 anodes can achieve the robust Na + storage in the half cells (5000 cycles at 5 A g –1 ) and extreme power output of 3134.9 W kg –1 in the full cell. This phase‐engineering approach enables the precise dimensional manipulation of the 1T TMDs, which further extends their application horizons as the cation host for the power‐oriented battery systems. Abstract : The metallic‐phase (1T) transition metal dichalcogenides monolayers are widely used in various fields, whereas their synthetic process relies on the empirical attempts under stringent conditions. The coherent gas‐phase electron injection and solid‐state alkali intercalation strategy to develop 1T‐MoX2 (X = S, Se) monolayers comprehensively investigates the underlying cation selection rules for the spatial compatibility optimization and 1T‐phase formation energy reduction.